Preparation and luminescence studies of thermosensitive PAN luminous fiber based on the heat sensitive rose red TF-R1 thermochromic pigment. (April 2017) - Jin, Yang; Shi, Chen; Li, Xiaoqiang; Wang, Yiwen; Wang, Fangfang; Ge, Mingqiao
Abstract: The aim of this study was to prepare and demonstrate a new kind of thermosensitive luminous fiber based on optical interference of thermochromic pigments. The surface morphology of a thermosensitive luminous fiber, containing Sr2 ZnSi2 O7 : Eu 2+, Dy 3+ ; Y2 O2 S: Eu 3+, Mg 2+, Ti 4+ ; and heat-sensitive rose red TF-R1 thermochromic pigment, was analyzed by scanning electron microscope (SEM). The X-Ray Diffraction (XRD) results revealed the crystal structure of the fiber samples and the synthesized rare-earth luminescence materials. There was no degradation of the crystalline phases in the blend when blending and spinning. The thermodynamic stability and dynamic phase structure were analyzed by Thermal Gravity Analysis (TGA) and Differential Scanning Calorimetry (DSC). This thermosensitive polyacrylonitrile (PAN) luminous fiber was stable below 200 °C. The fluorescence spectra, reflectivity spectra were measured to reveal the phosphorescence and thermochromism, and visual testing was also performed. The phosphorescence colors of the thermosensitive luminous fiber were directly related to the temperature. The prepared fiber samples had a red emission at room temperature, and because of the inner phase transition of the heat-sensitive rose red TF-R1 thermochromic pigment on heating, the fiber samples became colorless with blue light emission. This novel thermosensitive luminous fiber has many potential applications in optical and thermal sensors. Highlights: A new kind of thermosensitive luminous fiber based on optical interference was prepared at first time. This thermosensitive luminous fiber could sense the heat and show different colors as well as the fluorescent colors in different temperatures.